Phosphatase Producing Microbes Associated with Fish and Shellfish in Trivandrum Coast - Eapen, Alex; K., Maya; K., Dhevendran; P., Natarajan (Fishery Technology, 2025)
Total heterotrophic bacteria and  fungi and  the phosphatase producing bacteria  and fungi  in  the gill, guts and muscle of fish  (Etroplus spp., Gerres sp. and Glossogobius sp.) and  viscera  and  mantle  of  shellfish  (Vellorita sp. and Perna sp.) were  studied.  The hydrographic  parameters of  the environment  from  where  the  fishes  were caught were also studied.  Except shellfish Perna  indica, all  the species studied harboured phosphatase producing  bacteria. The  gut portion of  finfish contained high amount of total heterotrophic as well as phosphatase producing bacteria.  The present study showed that the phosphatase producing bacteria  mainly belonged  to Bacillus, Vibrio, Micrococcus and Corynebacterium spp. Moraxella showed maximum growth at 5% salt concentration. Moraxella and Aeromonas were sensitive towards mercury while 45% of Vibrio showed growth at 0.4 ppm mercury.